The inclusion of rotational acceleration in alpine helmet testing methodology - Dawson, L.; Post, A.; Hoshizaki, T. B. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Alpine skiing is a popular winter sport in which concussion has been found to be a common injury [1]. Concussion has been identified through research to be associated with rotational acceleration, however current impact testing standards such as ASTM F2040 and CE-EN 1077 do not measure this variable [2]. The purpose of this study was then to develop a methodology for alpine helmets to measure rotational acceleration using impact conditions with the highest risk of injury. Methods: In this study a large alpine helmet tested to ASTM 2045 was fitted on to a Hybrid III headform and impacted using a linear impactor at 5 sites that have been shown to have a high risk of concussion [2]. The impact velocity chosen was 8 m/s with a modular elastic programmer impact cap. Results: For sites 1-5, the linear acceleration was found to be: 206.3, 206.1, 225.1, 184.9, and 176.6g respectively. Rotational acceleration values were found to be 9753, 19317, 20761, 23661, and 15462 rad/s2 for site 1-5. Discussion: A methodology employing sites associated with high risk of concussion based on linear and rotational values was used to determine the safety of an alpine helmet. Based on Zhang et al (2004), the results of this study found an 80% risk of concussion for all sites for both peak linear and rotational acceleration [3]. The site with the highest risk was site 4, at the rear of the helmet outside of the centre of gravity. This location had the highest risk for concussion as it had the greatest dynamic response for rotational acceleration at 23661 rad/s2. These results demonstrate a high risk of concussive injury even while using current helmets in moderately high velocity impacts. A standard employing noncentric impacts and reporting rotational acceleration would be beneficial in decreasing the risk of injury. It is therefore suggested that a helmet test protocol including a rotational component would encourage helmet design to take into account that mechanism of injury to decrease the risk of concussion.